The Interplay of Digitalization, Deviant Behaviour, and Employee Performance - Carnelia, Yafia; Noermijati (Jurnal Kewirausahaan dan Inovasi, 2025)
In the era of rapid technological advancement, digitalization has become a crucial element for improving organizational efficiency and competitiveness. Understanding its impact on employee behavior and performance is essential, particularly for companies undergoing digital transformation. This study was conducted with the aim of determining the effect of digitalization on employee performance with deviant behaviour as a mediating variable on PLN UP3 Malang employees. The respondents in this study were 101 people, all of whom were permanent employees. The sampling technique used saturated sampling. Data were taken using direct distribution of printed questionnaires. Data processing used the SEM (Structural Equation Model) method with the SmartPLS version 4 application. The results of this study indicate that digitalization has a significant positive effect on employee performance, digitalization has a negative effect on deviant behaviour, deviant behaviour has no effect on employee performance, and deviant behaviour does not mediate the effect of digitalization on employee performance. These findings imply that the implementation of digitalization should be continued and optimized to boost performance, while also being accompanied by strategies to minimize potential negative behaviors in the workplace.